Retroauricular Advancement Flap In Single Stage Auricular Defect Reconstruction - Mirta Hediyati Reksodiputro; Trimartani Koento; Dwi Wahyu Manunggal (eJournal Kedokteran Indonesia, 2021)
Auricular defects must be treated early and properly because they may interfere with facial symmetry. Retroauricular skin is an ideal flap source for a non-reduction reconstruction procedure of the upper, middle, and lower auricular defects. Auricular reconstruction aims to achieve good anthropometric and aesthetic ear unit. The purpose of this case report is to present a reconstruction of auricular defects using the rectroauricular flap that results in a favorable aesthetic and normal anthropometric dimensions of the auricular. We report a case of auricular defect caused by post-excision of keloid located in the helical and antithetical area of the middle third of the right auricular, using a retroauricular flap. Normal values of the auricular’s anthropometric measurements were achieved, followed by a complete aesthetic ear unit. Retroauricular flaps are suitable for reconstructing partial auricle defects in the helical rim, temporal area, and conchae. Keywords: auricular defect, retroauricular flap, aesthetic ear unit, auricular anthropometry.   Jabir Retroaurikular untuk Rekonstruksi Defek Telinga Abstrak Daun telinga berperan penting pada simetri wajah sehingga defek di daun telinga harus ditangani dengan baik sejak dini. Kulit retroaurikular merupakan sumber jabir ideal untuk rekonstruksi tanpa reduksi pada defek daun telinga bagian atas, tengah, dan bawah. Rekonstruksi daun telinga bertujuan untuk mendapatkan hasil yang baik secara antropometri dan estetika unit telinga. Tujuan laporan kasus ini adalah menunjukkan hasil yang baik berdasarkan unit telinga estetik dan dimensi normal antropometri pada rekonstruksi defek daun telinga menggunakan jabir rektroaurikular. Dilaporkan satu kasus defek telinga pasca-eksisi keloid, di area heliks dan antiheliks sepertiga tengah daun telinga kanan, menggunakan jabir retroaurikular. Didapatkan nilai normal pada pengukuran antropometri telinga dan kelengkapan estetika unit telinga. Jabir retroaurikular baik untuk rekonstruksi defek telinga parsial di lengkung heliks, area temporal, dan konka. Kata kunci: defek aurikular, jabir retroaurikular, unit telinga estetik, antropometri daun telinga.